Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh. Issue Volume 67:Issue S2(2022) (13th June 2022) - Yau, Yvonne Y.Y.; Xin, Pei; Chen, Xiaogang; Zhan, Lucheng; Call, Mitchell; Conrad, Stephen R.; Sanders, Christian J.; Li, Linwei; Du, Jinzhou; Santos, Isaac R.
Abstract: Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore‐water‐derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to the ocean (outwelling) of 202 ± 160 and 78 ± 75 mmol m −2 d −1 of DIC and TA, respectively. The TA : DIC concentration ratio in the creek waters was 1, implying TA production from anaerobic mineralization in sediments. The lateral TA exports were comparable to the local (94 ± 48 mmol m −2 d −1 ) and national ( 50 mmol m −2 d −1 ) organic carbon burial. High TA exports could locally increase the ocean buffering capacity and contribute bicarbonate to the coastal ocean, acting as a long‐term carbon storage. Pore water traced by radon contributed 28–37% and 58–69% of DIC and TA exports. Separating the two major DIC components (i.e., CO2 emissions and alkalinity exports) is essential to resolve the carbon sequestration potential from saltmarshes. Here, dissolved CO2 emissions to the atmosphere accounted for 3–5% of total DIC outwelling. CH4 emissions played a minor role offsetting around 0.3 to 6% of the carbon sequestration. Overall, we demonstrate that alkalinity export into the ocean can be an overlooked carbon sequestration pathway in saltmarshes at rates comparable to carbon burial.